Library and Information Services for People with Disabilities in Academic Libraries on the Example of the Library of the University of Sarajevo – Faculty of Philosophy - Nihada Bećirović (Bosniaca)
Goal: The main goal of this paper is to examine and analyse in detail the existing services for people with disabilities at the Library of the University Sarajevo – Faculty of Philosophy, physical access to the building, access to the funds, content, and services, and on that track recognize possibilities of further improvement of services for blind and visually impaired users of the Library. Methodology: As a sample for this research the Library of the University Sarajevo – Faculty of Philosophy was chosen to analyse services that the Library offers to blind and visually impaired students, starting from the definition of disability of the United Nations Convention on the Rights of Persons with Disabilities and IFLA’s Glossary of Terms and Definitions, followed by IFLA’s Library Services to People with Special Needs Section. This research is based on selected IFLA guidelines Access to libraries for people with disabilities, which starts from the library’s environment, key categories from its physical space to access to materials and services. The paper also discusses the guidelines of the Library for the blind in the information age: Guidelines for the development of functions and services that provide an overview of all significant aspects of library and information services for the blind, from their historical development, legal and strategic frameworks on which such services directly depend, to users, staff, and the development and management of collections and services. Based on the IFLA guidelines, the paper analyses the following key categories: physical access to the Library’s premises, materials, assistive technology, trained staff, websites, and cooperation with other institutions, strategic documents, and evaluation. In addition to international acts, the paper also examines BH key regulations, such as the Law on Prohibition of Discrimination, which explicitly mentions this category of persons. Results: The analysis showed a significant adaptation of services to selected key categories, but also revealed the possibilities of improving these services, which are listed in the Conclusion, and recognized substantial successful segments of serving other users with disabilities, not only blind and visually impaired users. Based on the analysis, in the last chapter of the paper, in the Conclusion, the possibility of applying the framework plan for the development of these services of the Library of the Faculty of Philosophy of the University of Sarajevo on other academic libraries in Bosnia and Herzegovina is highlighted, and it points to the importance of cooperation with other institutions that serve blind and visually impaired users, and with whom it is possible to exchange resources for work, assistive technology of different types, but also experiences in working with users with disabilities. Originality: This paper presents selected IFLA guidelines for people with disabilities as a theoretical basis. The development of the themed services of this Library can serve as a model for other academic libraries in the BH environment.